TINGKAT LITERASI KEUANGAN DIGITAL (STUDI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM UNIVERSITAS ISLAM NEGERI MATARAM) - Gita Yuliana Aulia; Safwira Guna Putra (Universitas Islam Negeri Mataram, 2023)
This study aims to measure and analyze the level of digital financial literacy of students at the Faculty of Islamic Economics and Business, State Islamic University of Mataram using the measurement indicators proposed by Chen and Volve. This research is a descriptive quantitative research using survey methods for data collection. Aplying proportional random sampling so that the sample is spread proportionally from the total population. Data analysis was carried out by calculating the total score obtained for each indicator divided by the ideal score multiplied by 100 percent. The results showed that the average digital financial literacy level was 73.46% or moderate scale according to the financial literacy measurement index from Chen and Volve. In addition, it is known that sociodemographic factors such as gender, age, parental income, and work experience affects the digital financial literacy levels. Where male students tend to have a higher level of digital financial literacy than female students. Based on the age level, the older the student the higher the level digital financial literacy. Furthermore, based on the amount of parents monthly income, students who have parents with higher income levels tend to have higher levels of financial literacy as well. And finally, based on work experience, it was found that the digital financial literacy level of students who had work experience tended to have a higher percentage than students who had never worked.